Fishing tactics and the effect of resource depletion and interference during the exploitation of local patches of flatfish. (11th August 2022) - Rijnsdorp, A D; Aarts, G; Hintzen, N T; van Rijssel, J C; Winter, A M; Poos, J J
Abstract: The fine-scale exploitation pattern of fishers and the interactions among fishing vessels determine their impact on exploited populations, habitats, and ecosystems. This study used a unique combination of high resolution data of fishing tracks (positions recorded at 1 and 6 min intervals) and catch rates of sole ( Solea solea ) and plaice ( Pleuronectes platessa ) per tow, to study how pulse trawl (PUL) and tickler chain beam trawl (TBT) fishers exploit patches of concealed flatfish. PUL and TBT fishers had similar tactics. Effort was concentrated in the core of the patch. PUL fishers trawled in a systematic manner with successive tows segments placed parallel to each other at a median distance of ∼200 m. In 45% of the cores, simultaneous trawling by multiple PUL vessels occurred. A total of 40% of the cores were revisited in the following week, of which 50% were re-exploited. Catch rate in the core was ∼50% higher than the background catch rate and decreased over time due to resource depletion and interference related to the response of flatfish to the fishing activities. Interference contributed up to 67% to the decline in catch rate and was larger in TBT than in PUL.